Generalized moving extrapolation of stochastic processes based on the totality of continuous and discrete observations with memory; Journal of Computer and Systems Sciences International; Vol. 39, Iss. 4 - Dyomin N. S. Nikolas S. (2000, 2000)
The problem of simultaneous moving extrapolation (forecast, prediction) is considered or stochastic processes with continuous time at an arbitrary number of future instants based on the totality of realizations of processes with continuous and discrete time, which depend on both the current and the past values of a nonobserved process.